Proceedings 2 The biodiversity of African plants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
ProceedingsThe biodiversity of African plants proceedings of the XlVth AETFAT Congress held in Wageningen, The Netherlands from22-27 August 1994, edited by L J G van der Maesen, X M van Her Burgt, J M van Medenbach de Rooy 1996 861pp ISBN0 7923 4095...